IMF Staff papers : Volume 23 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1976)
This chapter presents a review article on the purchasing power parity (PPP) theory of exchange rates. The PPP theory involves the ratio of two countries' price levels or price indices times a base period exchange rate as the most important variable determining the exchange rate, but it allows both for other explanatory variables and for random influences. Criticisms of PPP include the existence of tariffs and transport costs, the role of income in exchange rate determination, and the existence of noncurrent account items in the balance of payments. The direction of causality (prices to exchange rates) has also been called into question. Several kinds of tests of the PPP theory have appeared in the empirical literature. One test demonstrates that the ratio of PPP to the exchange rate is systematically related to differences in per capita income across countries. Other tests correlate time series of PPP and the exchange rate or perform a comparative-static comparison of the two variables over time.